Unraveling the palindromic and nonpalindromic motifs of retroviral integration site sequences by statistical mixture models - Miklík, Dalibor; Grim, Jiří; Elleder, Daniel; Hejnar, Jiří (Genome research, 2023)
A weak palindromic nucleotide motif is the hallmark of retroviral integration site alignments. Given that the majority of target sequences are not palindromic, the current model explains the symmetry by an overlap of the nonpalindromic motif present on one of the half-sites of the sequences. Here, we show that the implementation of multicomponent mixture models allows for different interpretations consistent with the existence of both palindromic and nonpalindromic submotifs in the sets of integration site sequences. We further show that the weak palindromic motifs result from freely combined site-specific submotifs restricted to only a few positions proximal to the site of integration. The submotifs are formed by either palindrome-forming nucleotide preference or nucleotide exclusion. Using the mixture models, we also identify HIV-1-favored palindromic sequences in Alu repeats serving as local hotspots for integration. The application of the novel statistical approach provides deeper insight into the selection of retroviral integration sites and may prove to be a valuable tool in the analysis of any type of DNA motifs.
Keywords: nukleotidy; integrace viru; nukleotidové motivy; Nucleotide Motifs; Virus Integration; Nucleotides